Specialty-related asymmetries in treatment and outcomes of younger patients with atrial fibrillation. (19th May 2022) - Ferreira, J; Parreira, L; Farinha, JM; Esteves, AF; Coelho, R; Pinheiro, A; Mesquita, D; Marinheiro, R; Amador, P; Lopes, A; Caria, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) is the most common arrhythmia and one of the most frequent motives for presentation in the emergency department (ED). However, there are still significant inequalities concerning its treatment. Purpose: We aimed to assess if management and outcomes of patients with AF differed according to the specialty to which they were referred at hospital discharge. Methods: We conducted a retrospective single-centre analysis including adult patients admitted to the ED in 2016 with the International Classification of Diseases codes correspondent to AF. Patients older than 75 years and those whose electronic medical file was not accessible were excluded. Patient referral at discharge was not based on any pre-specified criteria but rather performed at the discretion of the physician in the ED. We divided our sample into 3 groups according to whom the patients were referred at hospital discharge: A) patients referred to an electrophysiologist; B) patients referred to a general cardiologist; and C) those referred to a non-cardiologist (general practitioner or internist). We assessed patient characteristics, delay to first appointment, treatment strategies as well as stroke and all-cause mortality at 3 years of follow-up. Results: Of the 372 patients initially screened, 184 were excluded due to age over 75 and 85 patients due to inaccessible medical records, resulting in a final sample of 103 patients with a median age of 65 (58-71) years and median CHA2DS2-VASc of 2 (1-3). At discharge from the index admission, one third of patients were referred to an electrophysiologist (group A), 41% to a general cardiologist (group B) and the remaining 26% to a non-cardiologist (group C). There were no significant differences in baseline characteristics or type of AF between the groups. The delay from index hospital admission to the first appointment was superior in groups A and B compared with C (3 and 2 vs 0 months, p=0.050). Patients referred to an electrophysiologist were more frequently started on a rhythm-control strategy compared with those referred to other physicians (71% vs 38% and 26%, p=0.004). Similarly, significantly more patients in group A underwent catheter ablation (47% vs 12% and 4%, p<0.001), around 2 years after the diagnosis (tendentially earlier than those in group B). At 3 years follow-up, mortality was higher in group C compared with the other groups (15% vs 0 in group A and 2% in group B, p=0.019). Stroke rates did not differ between groups. Conclusion: In this group of AF patients, referral to an electrophysiologist at discharge was associated with a higher rate of a rhythm-control strategy, including catheter ablation. In the long-term, those patients showed better survival. These results suggest that, in patients under 75 years, an earlier referral to an electrophysiologist might be beneficial.